THE EFFECTS OF DRYING AND SHELLING ON ASPERGILLUS FLAWS INFECTION AND AFLATOXIN PRODUCTION OF MAIZE* - O.S. DHARMAPUTRA (SEAMEO BIOTROP, 1997)
The effects of drying and shelling on Aspergillus flaus infection and aflatoxin production of maize stored under laboratory conditions were investigated together with the intactness of grain and change of moisture content during the storage period. Fully matured maize var. Arjuna and CPI-2 were harvested at 90 and 97 days after planting, respectively, after which they were unhusked and divided into 4 pans. The 1st and the 2nd parts were sun dried up to 20^ moisture content (m.c.) and then shelled and re-dried up to 17 and 14% m.c.. respectively. The 3rd part was sun dried up to 17% m.c. and then shelled but not re-dned. The 4th pan was sun dried up to 17% m.c. and then shelled and re-dried up to 14% m.c. The maize was sun dried by spreading either the cobs or the kernels on the paved floor. The nail-down wood and mechanical sheller were used for shelling the maize. After drying and shelling, maize samples were stored in the jars which were covered with muslin cloth for 3 months under laboratory conditions. A. flavus was isolated using dilution method on Aspergillus Flavus and Parasiticus Agar (AFPA). The damaged kernel analysis was carried out at the beginning of storage to obtain the percentage of damaged kernel caused by shelling. The m.c. and aflatoxin were determined using oven and High Performance Liquid Chromatography (HPLC) methods, respectively. The m.c. decreased at 1 month of storage and then it was almost constant at 2 and 3 months of storage. The percentage of damaged kernels of maize var. CPI-2 was higher than those of var. Arjuna. The percentage of damaged kernels of maize shelled at 20% m.c. was higher than that shelled at 17% m.c. The percentage of damaged kernels of maize shelled by mechanical sheller was higher than that shelled by nail-down wood.*Paper presented at the Symposium on Pest Management for Stored Food and Feed, 5 -7 September 1995 Bogor, Indonesia.